Energy and environmental performance of a near-zero-effluent rice straw to butanol production plant. Issue 2 (15th March 2021) - Dutta, Sambit; Ghosh, Shiladitya; Manna, Dinabandhu; Chowdhury, Ranjana
ABSTRACT: Present article focuses on the energy and environmental performance of a rice straw (RS) biorefinery producing bio-butanol as the main product, ethanol and acetone as the by-products and combined heat and power. The analysis highlights the strategic usage of RS-derived glucose and xylose as primary substrates for biobutanol production. The principle of utilization of total carbon and the fulfillment of the criterion of zero-waste management has been followed along with the generation of in-house energy to offset the energy expenditure and reduce CO2 emission. The overall yields of butanol, ethanol and acetone are 28.53kg, 0.84kg and 6.61kg respectively from 100kg RS. By performing energy analysis in this system for 100kg RS, energy content of lignin, extractives and biogas introduced to CHP have been estimated to be 674.78MJ. Net energy input to the steam turbine of the CHP is 539.83MJ and the outputs of electricity and heat energy are 130MJ and 194MJ, respectively. While the energy efficiency of CHP is 87%, the overall efficiency of the biorefinery through generation of alcohol/solvents and recovery of waste energy in the CHP is 68.2%. Due to the substitution of gasoline by butanol and through electricity generation, reduction of CO2 emission by 36.14kg is possible. GRAPHICAL ABSTRACT: UF0001